2015
DOI: 10.1016/j.seares.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution patterns and movements of Holothuria arguinensis in the Ria Formosa (Portugal)

Abstract: Holothurian populations are under pressure worldwide because of increasing demand 3 for beche-de-mer, mainly for Asian consumption. Importations to this area from new 4 temperate fishing grounds provide economic opportunities but also raise concerns 5 regarding future over-exploitation. Studies on the habitat preferences and movements 6 of sea cucumbers are important for the management of sea cucumber stocks and 7 sizing of no-take zones, but information on the ecology and behaviour of temperate 8 sea cucumber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 41 publications
3
31
0
Order By: Relevance
“…It consists of a sandy habitat (44.5 % coverage) and a seagrass habitat (35.6 % coverage). More details about the study area can be found in Siegenthaler et al (2015).…”
Section: Study Areamentioning
confidence: 99%
See 4 more Smart Citations
“…It consists of a sandy habitat (44.5 % coverage) and a seagrass habitat (35.6 % coverage). More details about the study area can be found in Siegenthaler et al (2015).…”
Section: Study Areamentioning
confidence: 99%
“…Tidal height at low tide was between 0.57 and 0.70 m during the first period and 0.36 and 0.60 m during the second one (source Instituto Hidrográfico). The whole study area was searched during each period of exposure (between 2 hours before low tide and 1 hour after it) and all holothurians found were marked in situ by means of scratching a code on their dorsal side (Reichenbach, 1999;Mercier, Battaglene, & Hamel, 2000;Navarro, García-Sanz, Barrio, & Tuya, 2013b;Siegenthaler et al, 2015) and released them at the same spot where captured. Although stress caused by marking and handling could result in increased initial activity (Shiell, 2006), scratching is considered as less invasive than other tagging methods (Conand, 1990;Kirshenbaum, Feindel, & Chen, 2006;Navarro, García-Sanz, & Tuya, 2014;Purcell, Agudo, & Gossuin, 2008;Schiell, 2006) and does not result in major behavioural changes (Mercier et al, 2000).…”
Section: Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations